Ontology of popular communication in the educational text between image and portrayal (مجلة إحالات, 2026)
Educational texts were enriched with deep insightful thinking and wide execution through their search for the norms within the nations’ social spirit and making it a mediator between the learner and the text, by the renewal of heritage models that were considered in ancient times as a lavish source and arepository for dialogue and exchange of ideas and views that were transmitted through generations.This heritage renewal shall be achieved through examining hermeneutic dynamics and explanatorystrategies, through which the texts were represented in a similar manner to the popular communicative methods that were included in the educational curricula of foreign languages,namely English, in the middle school levels, being the corner stone for the students’ terminologyand lexical connotation learning. Among the achieved results: neglecting some of the popular aspects which rooting the educational subject, such as stories and their style, while remaining oblivious to the simple popularmechanisms that help to control the learner’s principles.